PERAN ORANG TUA DALAM PENERAPAN STRATEGI KELUARGA DWIBAHASA SEBAGAI UPAYA PELESTARIAN BAHASA SASAK - Baiq Yulia Kurnia Wahidah; Wahidatul Murtafi’ah; Evi Safitri Yulandari (LPPM Institut Pendidikan Nusantara Global, 2026)
The shift from regional languages ​​to the national language is now a widespread phenomenon in the domestic sphere of the Sasak community. This study aims to explain the role of parents in implementing a bilingual family strategy (bilingualism) as a concrete effort to maintain and preserve the Sasak language within the family environment. The approach used was descriptive qualitative. Data were collected through in-depth interviews, participant observation, and open-ended questionnaires with Sasak parents in Lombok. Field findings indicate that parents implement three main strategies: the One Parent, One Language (OPOL) method, limiting the scope of language use (Sasak for the domestic sphere), and guided code-switching. The main obstacles faced include the dominant use of the national language and the lack of Sasak-language educational media for children. The consistent implementation of the bilingual strategy has proven effective as the first foundation for preventing language shift.